Improving English Grammar Mastery of Madrasah Diniyah Students through EGRA-Based Mentoring - Khudriyah Khudriyah; Nur Munir; Julianne Kamelia Riza; Ati Dingpanoh; Ainur Rofiq (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2026)
This community service program aims to improve the English grammar mastery of Madrasah Diniyah (Madin) students at STIT Al-Urwatul Wutsqo Jombang through mentoring using the EGRA (Exposure, Generalization, Reinforcement, and Application) method. The program was conducted in response to students’ low grammar proficiency resulting from their religious educational backgrounds and limited exposure to formal English learning. The EGRA method was applied as a gradual, participatory, and contextual grammar learning approach to enable students to independently understand and apply grammatical rules. This program involved 26 Madin students and employed a quantitative design using pre-test and post-test instruments. Data were analyzed using descriptive statistics and a paired sample t-test. The results indicate a significant improvement in students’ grammar achievement after the mentoring program, as shown by an increase in the mean score from 44.81 in the pre-test to 64.04 in the post-test. Statistical analysis also revealed that the calculated t value was higher than the t table value (9.836 > 2.05954) with a significance level below 0.05. These findings confirm that the EGRA method is effective in enhancing grammar mastery, learning motivation, and students’ confidence. This community service activity contributes an adaptive grammar mentoring model for students with non-general educational backgrounds, although it remains limited in terms of participant number and the scope of grammatical materials